PARTISIPASI MASYARAKAT DALAM MITIGASI BENCANA BANJIR DAN LONGSOR DI KABUPATEN SUMEDANG: LITERATURE REVIEW (2019–2025) - Aidil, Adji; Wahab, Aridla; Syariq, Muhamad Azriel; Hidayat, Raishard Fadil; Setiawan, Edi (JRPA - Journal of Regional Public Administration, 2025)
This study aims to systematically review the literature on community participation in flood and landslide disaster mitigation efforts in Sumedang Regency between 2019 and 2025. Using the Systematic Literature Review (SLR) method, six scientific articles were analyzed to explore the forms, effectiveness, and challenges of community involvement in disaster risk reduction. The findings reveal that community participation predominantly occurs during the implementation phase, while participation in decision-making, evaluation, and utilization of outcomes remains limited. Contributing factors include limited disaster literacy, inadequate infrastructure, and insufficient institutional support. Although national regulations such as Law No. 24 of 2007 and Government Regulation No. 21 of 2008 emphasize community engagement in disaster management, practical application at the local level still encounters significant challenges. Strengthening institutional capacity, increasing disaster education, and promoting inclusive collaboration across sectors are essential to fostering meaningful and sustainable community participation